Hobby, career or vocation? Meanings in sports coaching and their implications for recruitment and retention of coaches. Issue 4 (4th July 2022) - Ronkainen, Noora J.; Ryba, Tatiana V.; McDougall, Michael; Tod, David; Tikkanen, Olli
ABSTRACT: Rationale/Purpose: Traditional European sports clubs are facing increasing pressures to professionalise their services, while also encountering difficulties in the recruitment and retention of the coaching workforce. We used the concept of meaningful work to explore why coaching is worthwhile to coaches and how they have responded to the changes in the structural and narrative context of their work. Methodology: Drawing on narrative inquiry, we explored the various meanings and justifications that athletics (track and field) coaches assign to coaching in Finland and England. Twenty-three coaches (8 women, 15 men) aged 22–86 participated in narrative interviews that were analysed using thematic narrative analysis. Findings: The younger coaches mainly constructed coaching as a hobby and more often placed value on personal benefits, whereas many older coaches described coaching as a vocation/calling and emphasised causes that transcend the self (e.g. tradition, duty and leaving a legacy). Practical implications: Understanding the diverse ways in which coaching is meaningful is vital for supporting the recruitment and retention of the coaching workforce in sport clubs. Research contribution: The study extends understandings of meaningful work in coaching and how coaching is shaped by the broader structural and ideological contexts of the work.